Effect of a Health Coach Intervention for the Management of Individuals With Type 2 Diabetes Mellitus in China: A Pragmatic Cluster Randomized Controlled Trial - Chapman, Anna; Browning, Colette J.; Enticott, Joanne C.; Yang, Hui; Liu, Shuo; Zhang, Tuohong; Thomas, Shane A. (Frontiers in Public Health, 2018)
Aim: To determine the effect of a health coach intervention for the management of glycemic control, as well as physiological, psychological and self-care outcomes of patients with type 2 diabetes mellitus (T2DM), compared with usual care. Methods: This pragmatic cluster RCT was conducted in the Fengtai district of Beijing from August 2011 to December 2013. Forty-one community health stations (CHSs) were cluster randomized (stratified geographically, 1:1 ratio) and eligible, randomly selected T2DM patients were sequentially contacted by CHSs. Control participants received usual care according to the Chinese Guideline for Diabetes Prevention and Management. Intervention participants received 18-months of health coaching based on principles of Motivational Interviewing (MI) plus usual care. Medical and pathology fees were waived for both groups. Outcome assessment was performed at baseline, 6, 12, and 18-months. The primary outcome was glycated hemoglobin (HbA1c); secondary outcomes encompassed a suite of physiological, psychological and self-care measures. Results: No differential treatment effect was found at 18-months for HbA1c (adj. difference −0.07, 95% CI −0.53 to 0.39, p = 0.769) or any specified secondary outcomes. Interestingly, both groups displayed a statistically and clinically significant within-group improvement of the same magnitude at 18-months for HbA1c (intervention: mean change −3.65, 95% CI −3.92 to −3.37; control: mean change −3.38, 95% CI −3.67 to −3.08). Conclusions: The lack of differential treatment effects observed indicate that it may be premature to recommend the routine delivery of health coach interventions based on MI principles for the management of T2DM in China. However, the large, comparable within-group improvement in mean HbA1c promotes the establishment of free, regular clinical health assessments for individuals with T2DM in China. Trial Registration: ISRCTN registry - ISRCTN01010526 (https://doi.org/10.1186/ISRCTN01010526)